Comparison of the anti-inflammatory effectiveness of dexamethasone as pre-surgical and post-surgical therapy in mandibular third molar surgery: A randomized clinical trial. - Daniella Núñez-Díaz; Victor Chumpitaz-Cerrate; Lesly Chávez-Rimache; Luis German-Santa Cruz (Universidad de Concepción., 2019)
Objective: To compare the anti-inflammatory effectiveness of dexa-methasone as pre-surgical and post-surgical therapy in mandibular third molar surgery. Materials and methods: Randomized clinical trial conducted in 60 patients in need of mandibular third molar extraction, ages ranging from 16 to 35 years old, at the Department of Oral and Maxillofacial Surgery of the Arzobispo Loayza National Hospital during the period of January-March, 2016. Patients were distributed in two randomized groups: Group A received 4mg dexamethasone intramuscular before the surgery, and Group B received the same medication post-surgery. Facial edema was assessed using the distance between facial points, trismus was evaluated using the interincisal distance, and pain intensity was determined using a Numerical Scale (NS). Results: Facial edema values were lower in Group A at 60 minutes (p=0.002) and after the first (p=0.001) and third days (p=0.009), compared to Group B. Regarding trismus, no significant differences between the groups were found. Regarding pain intensity, the highest point was recorded at 6 hours in both groups; however, no significant differences between the groups were found. Conclusion: Pre-surgical dexamethasone administration produced a significantly greater reduction in facial edema after mandibular third molar surgery.